2020
DOI: 10.1007/s13365-020-00904-6
|View full text |Cite
|
Sign up to set email alerts
|

Direct antivirals and cognitive impairment in hepatitis C: a clinical-neurophysiologic study

Abstract: Cognition was assessed in hepatitis C virus (HCV) patients, who did not meet the criteria for a minimal hepatic encephalopathy. Their liver function was compensated. We then disentangled potential cognitive changes associated with a sustained virologic response at 12 weeks (SVR-12), following treatment with direct antiviral agents (DAAs). We studied 23 selected HCV patients with a battery of standard neuropsychological tests, and with recordings of the P300 wave, a cerebral potential of “cognitive” significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…In a small population, elimination of HCV by DAAs has been shown to improve anxiety and de-pression [98], although another study could not find an impact on anxiety or depression during or after HCV treatment by DAA [99]. Other studies have evidenced the possibility of an improvement in cognitive functions after viral eradication by DAA [100,101]. A recent study evaluated various cognitive areas using psychometric tests comparing patients with treatment-naive HCV or HCV treated with DAA and heathy individuals found that HCVpositive patients performed significantly differently from healthy controls, but no difference was found between untreated HCV and DAA-treated patients.…”
Section: Cognitive Dysfunction Psychiatric Manifestations and Quality Of Lifementioning
confidence: 99%
“…In a small population, elimination of HCV by DAAs has been shown to improve anxiety and de-pression [98], although another study could not find an impact on anxiety or depression during or after HCV treatment by DAA [99]. Other studies have evidenced the possibility of an improvement in cognitive functions after viral eradication by DAA [100,101]. A recent study evaluated various cognitive areas using psychometric tests comparing patients with treatment-naive HCV or HCV treated with DAA and heathy individuals found that HCVpositive patients performed significantly differently from healthy controls, but no difference was found between untreated HCV and DAA-treated patients.…”
Section: Cognitive Dysfunction Psychiatric Manifestations and Quality Of Lifementioning
confidence: 99%
“…In patients with suspected HCV-AND, tests that can be used to analyze the various cognitive domains are: Verbal learning and episodic memory: Rey auditory verbal learning test, Hopkins verbal learning test total recall, brief visual memory test revised total recall, digit forward span, verbal learning and memory test; Working memory: digit backward span, letter number sequencing, paced auditory serial addition task; Visuospatial skills and planning: Rey-Osterrieth complex figure test (ROCF) in the immediate trial; Lexical skills and executive functions: phonemic and the semantic verbal fluency tests, color-word-interference test (Stroop), trail making test part B, Wisconsin card sorting test, ROCF in the 10-min delayed recall trial; Logical thinking: verbal judgment test; Non-verbal intelligence: Horn’s performance test system[ 67 - 69 ].…”
Section: Diagnostic Strategies In Hcv-andmentioning
confidence: 99%
“…The direct-acting antiviral agents (DAAs) are a set of medications used to treat patients infected by the HCV. The summary of study characteristics and quality assessment of the 12 [29][30][31][32][33][34][35][36][37][38][39][40] included studies are presented in Table 2. Two of them were considered high quality, whilst the remaining ten others had ratings ranging from 4 to 6 stars, suggesting moderate quality.…”
Section: Significance Statementmentioning
confidence: 99%
“…Nine of the studies only evaluated it at the end of DAAs treatment. 29,[31][32][33][34][35][38][39][40] The other studies evaluated it twice-during, soon after the end, or after the end of DAAs treatment. 30,36,37 Amongst the results related to the cognitive effect of DAAs treatment, some studies had one or two control groups of healthy subjects, subjects coinfected with HIV and/or subjects with another clinical condition.…”
Section: Measurements Of Neuropsychological Outcomes Across Studies and Control Groupsmentioning
confidence: 99%
See 1 more Smart Citation